The role of political connection to moderate board size, woman on boards on financial distress - Dian Anita Nuswantara; Fachruzzaman; Riski Dwi Prameswari; Suyanto; Rusdiyanto Rusdiyanto; Ignatia Martha Hendrati (Cogent Business & Management, 2023)
This study aims to obtain empirical evidence of the effect of Board Size, Woman on Boards on Financial Distress, as well as the Role of Political Connections in Moderating Board Size, Woman on Boards on Financial Distress. This study seeks to identify the effect of Board Size, Woman on Boards on Financial Distress, and the Role of Political Connections in Moderating Board Size, Woman on Boards towards Financial Distress. This study uses a quantitative approach with a population and research sample using companies listed on the Indonesia Stock Exchange in 2016-2021. This study collects Board Size, Woman on Boards on Financial Distress from data on the Indonesia Stock Exchange website and companies from 2016-2021 and utilizes Google search. The data analysis method in this study uses the Regression Ordinary Least Square analysis method, Fixed Effects, Random Effects, Robust with Stata Software. Stata software is one of the Regression completion procedures that has a high degree of flexibility in research that links theory and data that can be carried out on variables in research. The first finding explains that board size does not have a negative effect on financial distress. The second finding explains that female commissioners have a positive and significant influence on financial distress. The third finding explains that the woman director has a positive and significant influence on financial distress. The fourth finding explains that the role of political connections strengthens and has a significant effect on board size on financial distress. The fifth finding explains that the role of political connections weakens and significantly influences the woman commissioner on financial distress. The sixth finding explains that the role of political connections weakens the influence of woman directors on financial distress. The practical implications of the results of this study can help company management and government in policy makers regarding the influence of board size, woman commissioners, woman directors on financial distress, and evaluate the role of political connections in moderating the effect of board size, woman commissioners, woman directors on financial distress. Theoretical implications of the results of this study can explain agency theory. As far as the results of the researchers' observations so far have not found research on the topic and to evaluate the role of political connections in moderating the effect of board size, female commissioners, female directors on financial distress
Keywords: G02; G32; G34; M1; Z1; 650; boated size; financial distress; Political connection; stata; woman on board